Human apolipoprotein E expression in Escherichia coli: structural and functional identity of the bacterially produced protein with plasma apolipoprotein E. - Vogel, T (1985)
Human apolipoprotein E (apoE) was produced in Escherichia coli by transforming cells with an expression vector containing a reconstructed apoE cDNA, a lambda PL promoter regulated by the thermolabile cI repressor, and a ribosomal binding site derived from the lambda cII or the E. coli beta-lactamase gene. Transformed cells induced at 42 degrees C for short periods of time (less than 20 min) produced apoE, which accumulated in the cells at levels of approximately equal to 1% of the total soluble cellular protein. Longer induction periods resulted in cell lysis and the proteolytic destruction of apoE. The bacterially produced apoE was purified by heparin-Sepharose affinity chromatography, Sephacryl S-300 gel filtration, and preparative Immobiline isoelectric focusing. The final yield was approximately equal to 20% of the initial apoE present in the cells. Except for an additional methionine at the amino terminus, the bacterially produced apoE was indistinguishable from authentic human plasma apoE as determined by NaDodSO4 and isoelectric focusing gel electrophoresis, amino acid composition of the total protein as well as its cyanogen bromide fragments, and partial amino acid sequence analysis (residues 1-17 and 109-164). Both the bacterially produced and authentic plasma apoE bound similarly to apolipoprotein B,E(low density lipoprotein) receptors of human fibroblasts and to hepatic apoE receptors. Intravenous injection resulted in similar rates of clearance for both the bacterially produced and authentic apoE from rabbit and rat plasma (approximately equal to 50% removed in 20 min). The ability to synthesize a bacterially produced human apolipoprotein with biological properties indistinguishable from those of the native protein will allow the production of large quantities of apoE for use in further investigations of the biological and physiological properties of this apolipoprotein.